METHOD FOR PRODUCING A CONNECTOR PART FOR ELECTRICAL INSTALLATIONS, CONNECTOR PART, AND CONNECTION OF A CONNECTOR PART TO A CABLE - RUDA, Matthias (2025)
The subject matter relates to a method for producing a connection part for electrical equipment, in particular for an on-board electrical system of a motor vehicle, comprising: deep-drawing a sheet-metal blank to produce a sleeve having a first end region and a second end region, the first end region having a bottom and the second end region being open, deforming, in particular pressing, the second end region to produce a tab, and introducing a through-hole into the tab. The subject matter also relates to a connection part for electrical installations, in particular for an on-board network of a motor vehicle, and to a connection of a connection part according to any one of the preceding claims to a cable formed from a plurality of wires or strands.